2018
DOI: 10.1144/sp471.7
|View full text |Cite
|
Sign up to set email alerts
|

An overlooked play? Structure, stratigraphy and hydrocarbon prospectivity of the Carboniferous in the East Irish Sea–North Channel basin complex

Abstract: Seismic mapping of key Palaeozoic surfaces in the East Irish Sea-North Channel region has been incorporated into a review of hydrocarbon prospectivity. The major Carboniferous basinal and inversion elements are identified, allowing an assessment of the principal kitchens for hydrocarbon generation and possible migration paths. A major Carboniferous tilt-block is identified beneath the central part of the (Permian to Mesozoic) East Irish Sea Basin (EISB), bounded by carbonate platforms to south and north. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 83 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…Paleozoic-sourced potential trapped within inversion structures is highlighted by a number of papers. In the Irish Sea, Pharaoh et al (2018) document Variscan inversion structures superimposed on Carboniferous fault blocks and highlight potential prospectivity within the deeply buried Carboniferous-Permian succession and around the margins of the oil-and gas-producing East Irish Sea Basin. Butler (2018) documents a regional seismostratigraphic framework of central-southern England that also includes a significant history of inversion and unconformity development within deeply buried sequences, including Variscan inversion over the Midlands Microcraton.…”
Section: Structural Complexity Of the Paleozoicmentioning
confidence: 88%
See 1 more Smart Citation
“…Paleozoic-sourced potential trapped within inversion structures is highlighted by a number of papers. In the Irish Sea, Pharaoh et al (2018) document Variscan inversion structures superimposed on Carboniferous fault blocks and highlight potential prospectivity within the deeply buried Carboniferous-Permian succession and around the margins of the oil-and gas-producing East Irish Sea Basin. Butler (2018) documents a regional seismostratigraphic framework of central-southern England that also includes a significant history of inversion and unconformity development within deeply buried sequences, including Variscan inversion over the Midlands Microcraton.…”
Section: Structural Complexity Of the Paleozoicmentioning
confidence: 88%
“…Carboniferous source rocks and Carboniferous, Permian and Triassic reservoirs and seals have formed a highly productive gas province in the East Irish Sea, the Southern North Sea (SNS) and onshore into the Netherlands and Germany since the 1960s (e.g. Meadows et al 1997;Glennie & Underhill 1998;Fraser & Gawthorpe 2003;Underhill 2003;Cameron et al 2005;Breunese et al 2010;Gast et al 2010;Kombrink et al 2010;Pletsch et al 2010;Pharaoh et al 2018;Figs 1 & 2). Substantial quantities of gas have been produced, e.g.…”
mentioning
confidence: 99%
“…Hydrocarbons were generated principally by organic-rich marine mudstones of Carboniferous age (Cowan et al 1999;Jackson et al 1995;Pharaoh et al 2016). The Carboniferous strata were deposited in basins associated with NNW-SSE extension, later folded along reactivated WSW-ENE Caledonian structures during the Variscan Orogeny.…”
Section: Geological Settingmentioning
confidence: 99%
“…Production to date has been exclusively from the Triassic, with a Sherwood Sandstone Group reservoir capped by the Mercia Mudstone Group (Figure 2). Aside from untested structures associated with this conventional petroleum system, future exploration might focus on prospective Palaeozoic targets such as the potential Carboniferous plays recently identified by Pharaoh et al (2016;in press). The EISB is also of interest in terms of its potential for carbon capture and storage (Armitage et al 2013;Lewis et al 2009), whereby emissions are captured from anthropogenic sources such as power plants, and injected to subsurface reservoirs for long-term storage.…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of the fold belt (and ancestral basin) into the offshore of the Irish Sea has been postulated on a speculative basis by numerous authors (e.g. Jackson et al 1995, Corfield et al 1996, Woodcock & Strachan 2012 but was first convincingly demonstrated by Pharaoh et al (2016bPharaoh et al ( , 2018 during the course of a review of Palaeozoic prospectivity in the Irish Sea for the 21 st C Exploration Roadmap Project (for a DECC/OGA/industry consortium). The location of exploration wells suggests that the prospectivity of the concealed fold belt has nevertheless long been recognised by the hydrocarbon industry.…”
mentioning
confidence: 99%